Membership in and Presence of Voluntary Organisations during the Swedish Fertility Transition, 1880-1949 - Johan Junkka (Historical Life Course Studies)
This article investigates the association between, participation in, and exposure to voluntary organisations and marital fertility during the European fertility transition from 1880 to 1949. This is achieved using individual-level longitudinal demographic data from northern Sweden linked with individual-level information on voluntary organisation membership and contextual level information on organisation activity. How living near an organisation influenced fertility is measured using mixed effect Cox regressions. The association to participation for both men and women is tested by matching members to a control group through propensity score matching before estimating differences in risks of another birth using Cox regressions. The results show that being exposed to an organisation was related to lower fertility. Joining a union or a temperance organisation showed even stronger negative associations, but only for male members, while female members showed no significant difference in fertility. The results suggest that reproductive decisions were not simple responses by the individual couple to structural changes but were also shaped within the social networks of which they were a part.